2018
DOI: 10.3390/su10020401
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable RC Beam-Column Connections with Headed Bars: A Formula for Shear Strength Evaluation

Abstract: Beam-column joints are critical regions for reinforced concrete (RC) frames subjected to earthquakes. The steel reinforcement is, in general, highly concentrated in these zones. This is why in many cases, headed bars are used. A headed bar is a longitudinal steel reinforcement whose end has a special button added to reduce the bonding length of the steel rebar. This paper establishes a formula predicting the shear strength of exterior RC beam-column connections where the beam longitudinal reinforcements use he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Tang et al [8] discussed modification of beam-column joint types namely square concrete-filled steel tubular (CFST) to overcome the decrease in beam-column joint capacity due to earthquake load. [9] discussed the prediction of shear strength in beam-column joints, especially in areas experiencing plastic joints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [8] discussed modification of beam-column joint types namely square concrete-filled steel tubular (CFST) to overcome the decrease in beam-column joint capacity due to earthquake load. [9] discussed the prediction of shear strength in beam-column joints, especially in areas experiencing plastic joints.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were held by [6], [7], [8], and [9] in observing the behaviour of beam-column joints will be used as the guidelines of the earthquake regulations to design a building structure. Certain elements of the building structure are allowed to undergo plastification as a means for dissipation of earthquake energy received by the structure, however, the structure must not collapse [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on structural damages caused by earthquakes worldwide have shown that the joint areas of RC frame-system structures are the most vulnerable [9]. A large number of the existing RC buildings have been constructed according to older regulations without particular planning for the reinforcement of the joints [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the role of steel fibers, the effects of the addition of fibers with different geometries and aspect ratios on the mechanical properties of SFRC might significantly vary [19]. Recently, other studies, including [20] have analyzed the shear strength.…”
Section: Introductionmentioning
confidence: 99%